Tunnels with rough walls and cavities - Vigne, Gabriele; Jönsson, Jimmy; Hacar, Fernando (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
Often the finishing surfaces of road tunnels (both gables and vaults) present not only important uniform roughness, but even holes that can be numerous and with significant size: usually in uncoated tunnel is where most uniform and major irregularities can be found whilst in rock tunnels excavated with blasting is where most holes can be found. This results in frictions coefficients with the tunnel walls that can be very high. The friction generated by the airflow in the ventilation can result in very important aerodynamic thrust requirements (with ventilation through jet-fans), which imply significant power consumption. Pressure losses in rugous tunnels and with the presence of cavities are analyzed for road tunnels with longitudinal ventilation through jet-fans, evaluating the aerodynamic thrust required to counter the corresponding losses.